2024
DOI: 10.1186/s13023-024-03035-x
|View full text |Cite
|
Sign up to set email alerts
|

Body weight, behaviours of concern, and social contact in adults and adolescents with Prader-Willi syndrome in full-time care services: Findings from pooled international archival data

Brian M. Hughes,
Anthony Holland,
Norbert Hödebeck-Stuntebeck
et al.

Abstract: Background Prader-Willi syndrome (PWS) is a complex genetic neurodevelopmental condition characterised by a range of debilitating and lifelong symptoms. The many physical and behavioural challenges that arise with adults with PWS often necessitate full-time (i.e., 24-hour) professional care support. However, despite the fact that many clinicians regard full-time PWS-specific care to represent best practice, relatively few studies have directly examined the benefits of such services. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…A recent survey of pooled international archival data also found an improvement in behavior after joining a full-time care service but, unlike our study, did not compare with people with PWS of the same age living at home. In addition, behavior was measured by a non-standardized tool, QOL was not measured, and the follow-up period was only a year [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of pooled international archival data also found an improvement in behavior after joining a full-time care service but, unlike our study, did not compare with people with PWS of the same age living at home. In addition, behavior was measured by a non-standardized tool, QOL was not measured, and the follow-up period was only a year [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean BMI was significantly lower in the group home residents (27.9 ± 7.1 kg/m 2 ) compared to age-matched individuals living at home (36.8 ± 12.7 kg/m 2 , p = 0.008) [ 11 ]. A recent survey of pooled international archival data showed that in people with PWS, there is a significant reduction in weight and BMI after joining a full-time care service, but the results were not compared with those of people with PWS living at home [ 12 ].…”
Section: Introductionmentioning
confidence: 99%